2019
DOI: 10.1111/ppl.12920
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide identification of the trihelix transcription factors and overexpression of Gh_A05G2067 (GT‐2), a novel gene contributing to increased drought and salt stresses tolerance in cotton

Abstract: We identified 102, 51 and 51 proteins encoded by the trihelix genes in Gossypium hirsutum, Gossypium arboreum and Gossypium raimondii, respectively. RNA sequence data and real‐time quantitative polymerase chain reaction analysis showed that Gh_A05G2067 (GT‐2) was highly upregulated under drought and salt stress conditions. Transient expression of GT‐2‐green fluorescent protein fusion protein in protoplast showed that GT‐2 was localized in the nucleus. The overexpression of GT‐2 conferred an enhanced drought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 85 publications
(93 reference statements)
7
27
0
Order By: Relevance
“…The higher concentration levels of the MDA in the leaf tissues of VIGS plants showed that the plants suffered more of oxidative stress compared with the wild types and the positively controlled plant under drought and salt stress conditions. The results obtained were in agreement with the previous findings in which the Gh_A05G2067 (GT-2) knocked out plants registered higher concentration levels of MDA, hydrogen peroxide and significant reduction on the concentration level of catalase (CAT), peroxidase (POD) (Magwanga et al 2019a). Therefore, these results suggested that GhOSCA1.1 gene may improve salt and drought tolerance of cotton.…”
Section: Ghosca Genessupporting
confidence: 92%
“…The higher concentration levels of the MDA in the leaf tissues of VIGS plants showed that the plants suffered more of oxidative stress compared with the wild types and the positively controlled plant under drought and salt stress conditions. The results obtained were in agreement with the previous findings in which the Gh_A05G2067 (GT-2) knocked out plants registered higher concentration levels of MDA, hydrogen peroxide and significant reduction on the concentration level of catalase (CAT), peroxidase (POD) (Magwanga et al 2019a). Therefore, these results suggested that GhOSCA1.1 gene may improve salt and drought tolerance of cotton.…”
Section: Ghosca Genessupporting
confidence: 92%
“…1b), an indication that CRI12 and MAR85 were less affected under salt stress compared to LAT40. Furthermore, Malondialdehyde (MDA) concentrations levels within the plants is an indication that the plants are suffering from oxidative stress, being MDA is a byproduct of lipid peroxidation [22]. The results obtained were in agreement to previous findings in which the knockdown of trihelix transcription factor in cotton reduced drought and salt stress tolerance and in turn accelerated the accumulation of various oxidants and MDA levels under drought and salt stress exposure [22].…”
Section: Oxidant and Antioxidant Evaluation Of The Three Upland Cottosupporting
confidence: 87%
“…showed significantly higher concentrations of proline and superoxide dismutase (SOD) compared to LAT40 ( Figure 1B), an indication that CRI12 and MAR85 were less affected under salt stress compared to LAT40. Furthermore, Malondialdehyde (MDA) concentrations levels within the plants is an indication that the plants are suffering from oxidative stress, being MDA is a byproduct of lipid peroxidation [22]. The results obtained were in agreement to previous findings in which the knockdown of trihelix transcription factor in cotton reduced drought and salt stress tolerance and in turn accelerated the accumulation of various oxidants and MDA levels under drought and salt stress exposure [22].…”
Section: Oxidant and Antioxidant Evaluation Of The Three Upland Cottosupporting
confidence: 87%
“…To investigate the gene regulatory network of alkali-salt stress response in upland cotton, we identified co-expressed gene sets via weighted gene co-expression network analysis (WGCNA) which can be used to find networks (modules) of highly correlated genes [30]. In the present study, 22,359 DEGs were used for WGCNA. In order to ensure a scale-free network, the power of β= 12 (scale free R2= 0.8740) was accurately selected by determination of soft-thresholding power ( Figure S3A orange red1 (Gene number: 1836, r= 0.95) module-SS3 stage in root).…”
Section: Co-expression Network and Module Constructionmentioning
confidence: 99%